The Story of Serratia Marcescens: Pathologic Risk Factors in Breast Implant Surgery - Yao, Caroline A; Wang, Diana; Kulber, David A (Archives of Plastic Surgery, 2014)
Serratia marcescens (S. marcescens) emerged as an opportunist in the setting of immunodeficiency in the 1970s, when serious infections occurred in San Francisco hospitals after USA. Navy experiments had aerosolized the bacteria to study biologic warfare. We investigate the risks of S. marcescens in San Franciscans who undergo mastectomy with implant reconstruction. From 2007 to 2011, the senior author took breast capsule cultures for all patients at the time of tissue expander exchange/explant. Of the 142 women who had reconstruction, 23 had positive cultures. Only the two patients who were positive for S. marcescens developed clinical infections that required explantation. Both had postoperative chemotherapy with transient neutropenia, and both had close ties to San Francisco. Clinical signs of infection emerged for both patients months after initial surgery, despite having previously well healed incisions. Other patients were culture positive for Pseudomonas, Proteus, Enterococcus and MRSA and did not develop require explant. While the link between San Francisco and S. marcescens is controversial, a patient's geography is a simple screening tool when considering postoperative risks, especially in the immunocompromised. Closer monitoring for neutropenia during chemotherapy, and a lower threshold to administer S. marcescens targeted antibiotics may be warranted in these patients.
Keywords: Breast implant; Serratia; Device removal; Infection; San francisco